2014
DOI: 10.4103/0973-6131.123481
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pain intensity and health related quality of life with Iyengar yoga in nonspecific chronic low back pain: A randomized controlled study

Abstract: Background:Nonspecific chronic low back (nCLBP) pain is prevalent among adult population and often leads to functional limitations, psychological symptoms, lower quality of life (QOL), and higher healthcare costs. The purpose of this study was to determine the efficacy of Iyengar yoga therapy on pain intensity and health related quality of life (HRQOL) with nCLBP.Aim of the Study:To compare the effect of Iyengar yoga therapy and conventional exercise therapy on pain intensity and HRQOL in nonspecific chronic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(113 citation statements)
references
References 10 publications
2
104
0
Order By: Relevance
“…Three studies reported methods of randomization but allocation concealment was not reported (Galantino 2004;Williams 2005;Nambi 2014), and two studies did not report details of randomization or allocation concealment (Williams 2009;Wattamwar 2013).…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies reported methods of randomization but allocation concealment was not reported (Galantino 2004;Williams 2005;Nambi 2014), and two studies did not report details of randomization or allocation concealment (Williams 2009;Wattamwar 2013).…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…This measures "the extent to which participants' lives are affected by whatever level of pain they felt", a concept related to but not the same as pain . Five studies reported mental and physical quality of life Cox 2010;Tilbrook 2011;Nambi 2014), and three studies reported depression (Galantino 2004;Williams 2009). Three studies reported some measure of clinical improvement (Saper 2009;Cox 2010;, and eight studies mentioned the presence or absence of adverse events (Sherman 2005;Williams 2005;Saper 2009;Williams 2009;Tilbrook 2011;Nambi 2014).…”
Section: Interventionsmentioning
confidence: 99%
See 3 more Smart Citations